Bali Jejaitan Ethno-Education Digital Book with Integrated Material on Identifying Geometric Solids in Mathematics Learning - Ni Ketut Arini; I Wayan Widiana; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2025)
Mathematics learning on spatial geometry material often feels abstract and less meaningful for elementary school students. The lack of contextual learning media and not linking the material to local culture is one of the causes of students' low conceptual understanding. This study aims to develop a digital book Etno Education based on Balinese jejaitan integrated with the material of identifying spatial geometry in mathematics learning. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 10 fourth grade students. . There are types of data that will be used in this study, namely qualitative data and quantitative data. The methods and instruments for data collection in this study used observation, interviews and questionnaires. Data were analyzed descriptively qualitatively and quantitatively. The results of the study showed that the digital book developed was included in the very feasible category and received a positive response from students. This book helps students understand geometric shapes through local cultural motifs. The implication of this study is the importance of developing interactive culture-based learning media to improve the quality of mathematics learning and preserve local culture simultaneously.